Evaluation of AChE inhibitors and dual AChE/GSK3-β inhibitor as Alzheimer’s disease treatment - Uras, G (2021)
Since the first patient affected by Alzheimer’s disease was reported in 1907, it became the worldwide leading cause of dementia. The disease is characterised by an initial accumulation of amyloid plaques, neurofibrillary tangles, along with cholinergic markers depletion. The currently available therapies for Alzheimer’s disease provide an amelioration of the cognitive symptomatology for a limited period, without altering the disease progression and outcome. Thus, a number of research projects are currently underway in order to find a therapy able to modify the disease course. For this, we evaluated the efficacy of different acetylcholinesterase inhibitors (XJP-1, SAD-2, SAD-6, and FAD), along with a dual acetylcholinesterase/Glycogen synthase kinase 3 β (16g), as potential Alzheimer’s disease treatment. To assess the efficacy of novel compounds we exploited two different Alzheimer’s models: Drosophila melanogaster, expressing either toxic amyloid peptides or hyperphosphorylated Tau protein, and differentiated SH-SY5Y cells treated with glyceraldehyde to induce Tau abnormal phosphorylation. The initial investigation on Drosophila Alzheimer’s models, carried out on XJP-1 only, showed contradictive results, proving beneficial effects, on both symptomatology and protein deposition, in fruit flies expressing amyloid peptides, but not in those flies presenting an hyperphosphorylated Tau protein. Subsequent testing of the novel cholinesterase inhibitors on differentiated SH-SY5Y model presenting an hyperphosphorylated Tau protein confirmed a not homogenous response to this class of compounds, in any of the assessed parameters, despite a similar level of inhibition of acetylcholinesterase enzyme. Conversely, inhibition of both AChE and GSK3-β enzymes resulted in an overall improvement of the GA induced defects. In particular, phosphorylation levels on residues S199 and S396 of Tau protein were reduced following 16g administration. Other than that, 16g administration rescued the neuronal-like morphology and prevented neuronal cell death in this particular model, which are fundamental parameters when treating Alzheimer’s disease. In summary, this work shows that the limited beneficial effects of cholinesterase inhibition for Alzheimer’s treatment, mainly on the amyloid-derived pathology, can be enhanced by dual-inhibition of both AChE and GSK3 β, which resulted in a significant improvement of the hyperphosphorylated Tau-induced defects along with reduction of amyloid peptides aggregation.